COMMUNITY CIVIC EDUCATION IN THE INDONESIAN BORDER AREAS (STUDY IN THE CENTRAL SEBATIK DISTRICT, NORTH KALIMANTAN PROVINCE) - Wahyudi Wahyudi; Idrus Affandi; Cecep Darmawan; Syarifudin Tippe; Poppy Setiawati Nurisnaeny; Jagad Aditya Dewantara (The Republic of Indonesia Defense University, 2020)
People who live in Indonesia's border area have conflict potential due to its condition that lagging in development, low level of welfare and human resources, and the access that is far from the central government. Therefore, this study outlines and develops the concept of civic education that aims to create ‘smart’ and ‘good’ citizens to create peace. Communities are based on local wisdom that is distinctive in society, especially communities who live in border areas. This study presents qualitative data from field research in the Indonesia-Malaysia border in Central Sebatik District, Nunukan Regency, North Kalimantan Province, which has polarization between different ethnic groups, religions, and citizenship. The results show that people who live in villages with different ethnicities, religions, and nationalities were able to live side by side peacefully. Those ethnic groups and religions are Bugis, Muslim, Timorese, Catholic, and Malaysian Bajau, which originated from religious values and tribal values that were believed can be developed in the Community Civic Education and has the potential to present defense resources at the border area.